Penambahan Berbagai Aras Selenium untuk Menurunkan Merkuri dalam Rumput yang Ditanam pada Tanah di Sekitar Pabrik Tekstil (Selenium Addition Level to Reduce Mercury in The Grass Planted on The Soil Adjacent to Textile Factory) - Ahimsa Kandi Sariri; R. Djoko Soetrisno; Subur Priyono Sasmito Budi (Faculty of Animal Science, Universitas Gadjah Mada, 2010)
The study was conducted to determine the level of Se that influenced the absorption of Hg by grasses and todetermine the optimal level of Se to reduce Hg absorption. Two species of grasses namely Panicum muticum andPennisetum purpureum, and 4 levels of Se namely 0, 1, 2, and 3 ppm, with 5 replications of each treatments were usedin this study. The experimental design was a Completely Randomized Design (CRD). Parameters measured were N total(Kjeldahl method), available P (Bray II method), exchangeable K (K in water method), Hg and Se content of the soil (AAS method). Samples of the forage were analyzed the Hg, Se, digestibility and crude protein (CP) content. Results ofthe study showed that species of grasses, level of Se and its interaction significantly (P<0.01) affected Hg content of the soil, Se and crude protein content of the forages. Level of Se significantly (P<0.01) affected Hg content of the forages while Se concentration on the soil were not afftected by level of Se but affected by spesies of grasses and interaction between level Se and spesies of grasses. Hg content of the soil (12.45 ppb) decreased after Panicum muticum cultivation (3.599 ppb) and however, they were significantly (P<0.01) different with the Hg content of the soil cultivated by Pennisetum purpureum (0.52 ppb). Hg contens of the Panicum muticum and Pennisetum purpureum were not detected under 0.54 ppb. Se contents of the soil increased after Panicum muticum cultivation (1.395 ppm) and were significant (P<0.01) different with cultivated by Pennisetum purpureum (1.585 ppm) also Se contents of the forages. Highest crude protein contents of the forages at the level Se 2 ppm for Panicum muticum (6.55%) and Pennisetum purpureum (6.88%). Conclusion of the study is addition of Se influence Hg absorbtion and level Se 2 ppm can be given to get thebest forages quality.(Key words : Selenium, Mercury, Panicum muticum, Pennisetum purpureum)